Pengembangan Purwarupa Colearn Untuk Pembelajaran Multimedia Siswa SMK Menggunakan Model User Centered Design - Galih Wisnu Murti; Retno Indah Rokhmawati; Ahmad Afif Supianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
SMK Negeri 1 Boyolangu is a vocational high school that conducts learning at home during the COVID-19 emergency. The delivery of learning material is carried out through school e-learning media and the implementation of video conference on certain learning materials. But on implementation, students still have difficulty understanding the learning material. Therefore, this study aims to develop a COLEARN mobile learning prototype for multimedia majors in vocational high schools. The development of this prototype was carried out using the User Centered Design (UCD) method by adding a profile analysis of students' mental models. UCD involves the end user directly in its development. The analysis stage of the use context carried out the identification of the mental model profile of students as the basis for developing interactions in the prototype. From this process, it is hoped that students will be more familiar with the prototype designs that have been developed. At this stage, a persona, empathy map and a user journey map are also created to identify the user's goals and tasks. In the implementation process of the solution design, a wireframe, mockup and prototype were designed to be evaluated using the usability method and the system usability scale. From the results of the evaluation, it was found that the effectiveness level was 100% with an efficiency of 0.13 tasks per second and a user satisfaction score of 71 with a good category on the SUS assessment criteria.